Teachers’ Voice on the Practical Learning Strategies for Young Learners with Poetry - Mahayanti, Ni Wayan Surya; Suwastini, Ni Komang Arie; Tuilan, Jeane; Dials, Jeanette (IJEE (INDONESIAN JOURNAL OF ENGLISH EDUCATION), 2024)
A recent study suggests that poetry might offer unique insights into improving English language development. Despite these benefits, many language teachers avoid using poetry since teaching English through poetry in non-English-speaking countries is difficult. Poetry's ability to support language development has been overlooked due to teachers’ challenges. This shows a serious lack of understanding of teachers’ pedagogical skills in using literature to educate. Large-scale quantitative studies have examined teachers' experiences and challenges. Nevertheless, this study focuses on what they consider crucial pedagogical factors in employing poetry in English classes. This qualitative survey includes 15 English teachers. A teacher questionnaire was given to discuss their needs in constructing poetry-based English language learning practices, and interviews were performed to examine kindergarten and elementary school English language learning. The findings portrayed that poetry improves pupils' listening and speaking skills and vocabulary building. In addition, they thought that songs/lyrics and poetry should be used more in teaching and learning. A thematic analysis showed how teaching strategies, poem selection, and impact are varied.